Cyclic dynamics drive summer movement ecology of snowshoe hares (Lepus americanus) - Miller, Hannah A.; Gobin, Jenilee; Boudreau, Melanie R.; Horne, Liam G.; Scholl, Lee E.; Seguin, Jacob L.; Sonnega, Samuel; Krebs, Charles J.; Boonstra, Rudy; Kenney, Alice J.; Jung, Thomas S.; Boutin, Stan; et al. (Frontiers in Ecology and Evolution, 2024)
Animals exhibit dynamic movement and activity in response to environmental variation including changes in reproductive opportunities, predation risk, or food availability. Yet, it remains unclear which factors are primary in affecting animal movement, and whether the relative importance of these factors are consistent through time. We tracked snowshoe hares (Lepus americanus) using GPS telemetry during eight summers spanning a hare population cycle (2015–2022) in southwestern Yukon, Canada, to determine associations between environmental variation and hare movement and home range size. Hare density varied 25-fold during the study and home range size increased markedly during low hare density, especially for males. Both sexes retained similar core space use and linearity of movements, but at low densities males had greater and more variable movement rates and time spent travelling. Trail cameras revealed that annual changes in hare movement were also correlated with relative abundance of lynx (Lynx canadensis) and coyotes (Canis latrans). However, hare detection rates within a season were not closely associated with seasonal variation in predator detection. Observed differences between male and female hares in some metrics highlighted that different life histories and reproductive behavior are likely the main drivers of hare movement dynamics. Therefore, fitness rewards associated with successful mate search and reproduction appear to outweigh risks associated with increased movement, even in highly variable environments where costs of prioritizing reproduction-related activities are notably high and variable.